The Impact of Facilities and Means of Transportation on Tourist Satisfaction at Monaco Park Sibiru-Biru Deli Serdang North Sumatra - Gloria Citra Christiany Br Sitepu; Abd. Rasyid Syamsuri; Arief Hadian (Garuda Prestasi Nusantara Consulting, 2023)
This study aims to analyze the effect of facilities and means of transportation on tourist satisfaction at Monaco Park Sibiru-Biru Deli Serdang, North Sumatra. The research method used in this research is quantitative. The research population is tourists in Monaco Park Biru-Biru, namely 300 visitors from January - March 2022. To determine the sample size of the known population, there are 300 tourists in Monaco Park Biru-Biru. With an error tolerance of 5%, the number of samples that will be used if calculated using the formula is 172 respondents. The results of the study show that facilities have a positive and significant effect on tourist satisfaction in Monaco Park Sibiru-Biru. Means of transportation have a positive and significant effect on tourist satisfaction in Monaco Park Sibiru-Biru. Simultaneously facilities and means of transportation have a positive and significant effect on tourist satisfaction in Monaco Park Sibiru-Biru. R Square (R2) shows the coefficient of determination is 0.719 (71.9%) meaning that the percentage of facilities, transportation facilities, and tourist satisfaction is 71.9% while the remaining is 28.1%.